(Meth)acrylate-based reinforced adhesive

By using modifiers of core shell structure and liquid polybutadiene end polymers, the problem of difficulty in dispersing enhancer in the acrylate-based adhesive composition is solved, achieving easy processing and significantly improved impact resistance.

JP2025503226APending Publication Date: 2025-01-30HENKEL KGAA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024544756
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-28
Filing Date
2023-01-30
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

In the existing acrylate-based adhesive composition, it is difficult to disperse the reinforcement uniformly, resulting in processing difficulties and increased costs, affecting the final performance.

Method used

Modifiers of the core shell structure, including polymer cores and at least two different polymer layers, combine liquid polybutadiene terminal polymers and other reinforcement components to form an improved acrylate-based adhesive composition to enhance its impact resistance.

Benefits of technology

The acrylate-based adhesive is easily mixed and dissolved, significantly improving the impact strength to achieve an increase of at least 50%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503226000001
    Figure 2025503226000001
  • Figure 2025503226000002
    Figure 2025503226000002
  • Figure 2025503226000003
    Figure 2025503226000003
Patent Text Reader

Abstract

A structural adhesive containing a core-shell toughening component that is miscible in a methylacrylic adhesive with at least one toughening agent that is not miscible in a methacrylic adhesive produced surprisingly improved impact resistance, especially in side impact testing.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to (meth)acrylate-based adhesive compositions that include a toughening agent that is soluble and / or miscible in (meth)acrylates, which toughening agent provides improved impact toughness performance. [Background technology]

[0002] Modern structural adhesives contain a variety of toughening agents to enhance performance with respect to impact resistance. Common toughening additives that have proven effective in improving performance characteristics such as impact resistance include butadiene styrene solid rubber particles sold commercially under the Blendex brand. Another known useful toughening agent is Kraton D1155, described by the manufacturer (Kraton Corporation) as a linear block copolymer based on styrene and butadiene with 40% bound styrene by weight. Kraton D1155 is supplied as porous pellets dusted with amorphous silica. Another commercially available useful toughening agent is Hypro RLP 200X168VTM, described by the manufacturer (CVC Thermoset Specialties) as a reactive liquid polybutadiene polymer terminated with methacrylate groups.

[0003] While such toughening agents may improve performance properties, they are not easily dispersed, miscible, or soluble in (meth)acrylates, resulting in various processability and cost issues. Thus, current (meth)acrylic (e.g., (meth)acrylate)-based adhesive compositions that use these commercially available materials (and other such materials) require additional time and expense to ensure that these solid materials are properly incorporated into the (meth)acrylate to provide the desired toughness. For example, failure to properly disperse these toughening agents in the respective adhesive compositions is expected to adversely affect the performance properties of the final adhesive composition.

[0004] It would therefore be particularly advantageous to include a toughening material that can be easily incorporated into (meth)acrylic adhesives, is easily miscible and / or soluble in (meth)acrylates, and provides improved impact resistance. The present invention addresses this problem and provides compositions that include toughening materials and toughening compositions that provide improved performance properties. Summary of the Invention [Means for solving the problem]

[0005] a) i. (Meth)acrylate Component ii. a core-shell impact modifier, from about 10% to about 25% by weight of the total composition, comprising a polymer core and at least two polymer layers surrounding the core, each layer having a different polymer composition than the other layers, at least one polymer layer comprising a polymer that is a gradient polymer, the gradient polymer being a copolymer of at least two different monomers (A) and (B) having a gradient of repeat units arranged from predominantly monomer (A) to predominantly monomer (B) along the copolymer; iii. about 10% to about 25% by weight of the total composition of a reinforcing component selected from the group consisting of polybutadiene rubber particles (Kraton D), liquid methacrylate terminated polybutadiene polymer (Hypro RLP), and combinations thereof; iv.Amine The first part includes: b) i. Epoxy, and ii. Peroxide The second part includes An adhesive composition comprising: An adhesive composition which, upon curing, exhibits at least a 50% increase in side impact strength as compared to a substantially identical composition lacking the impact modifier.

[0006] a) i. (Meth)acrylate Component ii. a core-shell impact modifier, from about 10% to about 25% by weight of the total composition, comprising a polymer core and at least two polymer layers surrounding the core, each layer having a different polymer composition than the other layers, at least one polymer layer comprising a polymer that is a gradient polymer, the gradient polymer being a copolymer of at least two different monomers (A) and (B) having a gradient of repeat units arranged from predominantly monomer (A) to predominantly monomer (B) along the copolymer; iii. about 10% to about 25% by weight of the total composition of a reinforcing component selected from the group consisting of polybutadiene rubber particles, liquid methacrylate-terminated polybutadiene polymers, and combinations thereof; iv.Amine The first part includes: b) i. Epoxy, and ii. Peroxide The second part includes An adhesive composition comprising the reaction product of An adhesive composition which, upon curing, exhibits at least a 50% increase in side impact strength as compared to a substantially identical composition lacking the impact modifier. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] (Detailed Description) The present invention aims to improve toughness properties, especially impact resistance properties, by incorporating a toughening component that is easily mixed into the methacrylate composition and surprisingly improves impact resistance. In general, the composition of the present invention may include the following components and ranges:

[0008] [Table 1]

[0009] In the context of this disclosure, a number of terms are used.

[0010] The term "(meth)acrylate" refers to both "acrylate" and / or "methacrylate."

[0011] The term "(meth)acrylic" refers to both "acrylic" and "methacrylic", or either one of them.

[0012] The term "monomer" refers to a polymer building block that has a defined molecular structure and can react to form part of a polymer.

[0013] The term "oligomer" refers to a molecule that contains at least two repeating units.

[0014] The term "hydrocarbon or hydrocarbyl group" refers to an organic compound composed of carbon and hydrogen. Examples of hydrocarbon groups include, but are not limited to, alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, tertiary butyl, isobutyl, etc., alkenyl groups such as vinyl, allyl, butenyl, pentenyl, hexenyl, etc., aralkyl groups such as benzyl, phenethyl, 2-(2,4,6-trimethylphenyl)propyl, etc., or aryl groups such as phenyl, tolyl, xylyl, etc.

[0015] The term "optionally substituted" in the term "optionally substituted hydrocarbon group" means that one or more hydrogens on the hydrocarbon group may be replaced with a corresponding number of substituents preferably selected from halogen, nitro, azide, amino, carbonyl, ester, cyano, sulfide, sulfate, sulfoxide, sulfone, sulfonic acid groups, and the like.

[0016] The term "glass transition temperature" refers to the temperature at which a polymer transitions between a highly elastic state and a glassy state. Glass transition temperature can be measured, for example, by differential scanning calorimetry (DSC).

[0017] The compositions of the present invention are generally two-part compositions (Part (A) and Part (B)) as described below, but may in some cases be one-part compositions.

[0018] <Part (A)> Part (A) includes at least one (meth)acrylic component (such as a methacrylate-based material); a toughening agent component including a core-shell impact modifier that is readily miscible with the methacrylic component, at least one additional toughening agent, and an amine. Other components can be added to Part (A), including stabilizers, cure accelerators, adhesion promoters, rheology modifiers, and other useful materials described herein.

[0019] <(Meth)acrylic component> The (meth)acrylic component may have the following formula: [ka] (wherein R is H, halogen, or C1-C 10 The compound may include any suitable material that includes at least one group having a substituent selected from the group consisting of a aryl group, a cyclic ...

[0020] Advantageously, this group is a (meth)acryloxy group. The term "(meth)acryloxy" is intended to refer to both acrylates and methacrylates where R is H or methyl, respectively. Useful amounts of the (meth)acrylic component typically range from about 20% to about 80% by weight of the total composition, desirably from about 30% to about 60% by weight of the total composition, and more desirably from about 40% to about 50% by weight of the total composition.

[0021] The (meth)acrylic component can be present in the form of a polymer, a monomer, or a combination thereof. When present in the form of a polymer, the (meth)acrylic component may be a polymer chain having at least one of the above groups attached thereto. These groups may be located at pendant or terminal positions on the backbone, or a combination thereof. Advantageously, at least two such groups may be present and located at the terminal 65 positions. The (meth)acrylic component may have a polymer chain composed of polyvinyl, polyether, polyester, polyurethane, polyamide, epoxy, vinyl ester, phenol, amino resin, oil-based resin, etc., or random or block combinations thereof, as known to those skilled in the art.

[0022] The polymer chain may be formed by polymerization of vinyl monomers. Specific examples of such vinyl monomers include methyl (meth)acrylate, (meth)acrylic acid, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhex ... Cylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, tolyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, stearyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate acrylate, 2-(meth)acryloyloxypropyltrimethoxysilane, (meth)acrylic acid ethylene oxide adduct, trifluoromethylmethyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethylmethyl (meth)acrylate, 2- Perfluoromethyl-2-perfluoroethylmethyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, 2-perfluorohexadecylethyl (meth)acrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, dipentaerythritol monohydroxypentaacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-Hexanediol diacrylate, neopentyl glycol diacrylate, pentaerythritol tetraacrylate, 1,2-butylene glycol diacrylate, trimethylolpropane ethoxylate tri(meth)acrylate, glyceryl propoxylate tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, tri(propylene glycol) di(meth)acrylate, neopentyl glycol propoxylate di(meth)acrylate, 1,4-butanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate and ethoxylated bisphenol A di(meth)acrylate. These monomers may be used alone or may be copolymerized in combination.

[0023] Particularly preferred (meth)acrylate ester monomers include those containing 1 to 8 carbon atoms in the alcohol portion of the ester group, such as 2-ethylhexyl (meth)acrylate, hydroxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, ethyl (meth)acrylate, 1,3-butanediol di(meth)acrylate (BDMA), butyl (meth)acrylate, and methyl (meth)acrylate (MMA).

[0024] <Core-shell impact modifier component> The core-shell impact modifier is desirably a "core-shell" graft copolymer. The shell portion may be polymerized from methyl methacrylate and optionally other alkyl (meth)acrylates, such as ethyl, butyl (meth)acrylate or mixtures thereof. Up to 40 weight percent or more of the shell monomers may be styrene, vinyl acetate, vinyl chloride, and the like. Additional core-shell graft copolymers useful in embodiments of the present invention are described in U.S. Patent Nos. 3,984,497, 4,096,202, 4,034,013, 3,944,631, 4,306,040, 4,495,324, 4,304,709, and 4,536,436, the entireties of which are incorporated herein by reference. Examples of core-shell graft copolymers include, but are not limited to, "MBS" (methacrylate-butadiene-styrene) polymers made by polymerizing methyl methacrylate (MMA) in the presence of polybutadiene or polybutadiene copolymer rubber. MBS graft copolymer resins generally have a styrene butadiene rubber core and an acrylic polymer or copolymer shell. Other useful core-shell graft copolymer resins include ABS (acrylonitrile-butadiene-styrene), MABS (methacrylate-acrylonitrile-butadiene-styrene), ASA (acrylate-styrene-acrylonitrile), all acrylic, SAEPDM (styrene-acrylonitrile grafted onto an elastomeric backbone of ethylene-propylene diene monomer), MAS (methacrylic-acrylic rubber styrene), and the like, and mixtures thereof.

[0025] The core-shell impact modifier comprises a polymer core and at least two polymer layers surrounding the core, each layer having a different polymer composition than the other layers, and at least one polymer layer comprises a polymer that is a gradient polymer, a gradient polymer being a copolymer of at least two different monomers (A) and (B) having a gradient of repeat units arranged from predominantly monomer (A) to predominantly monomer (B) along the copolymer.

[0026] The core-shell impact modifier comprises particles having a particle size of 170-350 nm and a pH of 6-7.5, and comprises one polymeric rubber core comprising at least partially crosslinked isoprene or butadiene and optionally styrene, and at least two polymeric layers, at least one of which is an outermost thermoplastic shell layer having a Tg greater than 25°C, each layer having a different polymeric composition.

[0027] The core-shell impact modifier comprises a polymeric rubber core surrounded by a polymer layer, the polymeric core layer having a glass transition temperature below 0°C and having a different polymer composition than the polymeric rubber core, the polymeric core layer being a gradient zone.

[0028] The core-shell impact modifier comprises at least one polymeric core layer and at least two polymeric shell layers, the polymeric core layer having a different composition than the polymeric shell layers, each shell layer having a different polymer composition than the other shell layers, and at least one polymeric shell layer is a gradient zone.

[0029] The core-shell impact modifier should comprise a polymeric rubber core having a glass transition temperature below 0°C, e.g., below about -10°C, desirably below about -20°C, advantageously below about -25°C, and most advantageously below about -40°C, e.g., from about -80°C to about -40°C.

[0030] The core-shell impact modifier should include a polymeric rubber core composed of one or more of isoprene or butadiene homopolymers, isoprene-butadiene copolymers, copolymers of isoprene (up to 98 percent by weight of vinyl monomers), and copolymers of butadiene (up to 98 percent by weight of vinyl monomers). The vinyl monomers can be styrene, alkylstyrene, acrylonitrile, alkyl (meth)acrylates, or butadiene or isoprene. Desirably, the core should be composed of either polybutadiene, copolymers of butadiene and styrene, or terpolymers of methyl methacrylate, butadiene and styrene.

[0031] In some embodiments, the core can also be covered by a core layer, which means that the polymer composition of the core layer has a glass transition temperature (Tg) below 0° C., such as below about −10° C., desirably below about −20° C., advantageously below about −25° C. Desirably, the core layer is a gradient polymer.

[0032] The core-shell impact modifier should have one or more shells, preferably two shells, at least the outer shell in contact with the thermoplastic matrix having a Tg of about 25° C. or higher, such as about 50° C. or higher.

[0033] The shell of the core-shell impact modifier may be composed of one or more of a styrene homopolymer, an alkylstyrene homopolymer, or a methyl methacrylate homopolymer, or a copolymer comprising at least 70% by weight of one of the above monomers and a copolymer comprising at least one comonomer selected from another alkyl (meth)acrylate of the above monomers, vinyl acetate, and acrylonitrile. The shell may be functionalized with, for example, anhydrides of unsaturated carboxylic acids, unsaturated carboxylic acids and unsaturated epoxides, such as maleic anhydride, (meth)acrylic acid glycidyl methacrylate, hydroxyethyl methacrylate, and alkyl (meth)acrylamides.

[0034] Gradient copolymers are produced by occupying a position between two layers, and in doing so, creating a gradient zone where on one side the monomer / polymer from the adjacent layer is more abundant, and on the other side the different monomer / polymer that will form the next layer is more abundant. Gradient zones between the core and shell, or between two polymer shells, can be formed, for example, by using monomers with different copolymerization parameters, or by reacting in semi-continuous mode under starvation-fed conditions, where the rate of monomer addition is slower than the rate of reaction. However, gradient polymers do not become the outermost layer of a core-shell particle.

[0035] The monomers used to form the gradient polymer are selected from the monomers cited for the core and each shell based on the functionality of the adjacent layers.

[0036] The Young's modulus of the polymer rubber core will always be lower than that of the other polymer layers, and the Young's modulus of the layers making up the gradient polymer will always be lower than that of the outermost layer.

[0037] The core-shell impact modifier should be in the form of microparticles having a rubber core and at least one thermoplastic shell, the particle size of which is generally less than 1 μm, advantageously between 50 nm and 500 nm, preferably between 100 nm and 400 nm, most preferably between 150 nm and 350 nm, advantageously between 170 nm and 350 nm.

[0038] Core-shell impact modifiers can be produced by emulsion polymerization. For example, a suitable method is a two-stage polymerization technique in which the core and shell are produced in two successive emulsion polymerization stages. If there is a further shell, another emulsion polymerization stage follows. The graft copolymer is obtained by graft polymerizing a monomer or mixture of monomers containing at least an aromatic vinyl, an alkyl methacrylate or an alkyl acrylate in the presence of a latex containing a butadiene-based rubber polymer. For more information on the method of producing such core-shell impact modifiers, see U.S. Pat. Nos. 9,068,036 and 9,714,314. Commercially available products of such core-shell impact modifiers are available under the trademark CLEARSTRENGTH from Arkema Inc., Cary, North Carolina. Arkema describes, for example, CLEARSTRENGTH XT100 as a methyl methacrylate-butadiene-styrene core-shell toughener. The product is compatible with a wide variety of monomers, disperses easily in most liquid resin systems, and provides toughening effects over a wide range of operating temperatures with limited impact on viscosity.

[0039] <Additional reinforcement> The compositions of the present invention also include at least one reinforcing component selected from "shellless" crosslinked rubbery particulates such as acrylonitrile-butadiene-styrene (ABS), methacrylate-butadiene-styrene (MBS), and methacrylate-acrylonitrile-butadiene-styrene (MABS). For example, BLENDEX 338 is an ABS powder from GE Plastics. Another example is Kraton D 1155, a linear block copolymer based on styrene and butadiene with 40% bound styrene by mass. Kraton D1155 is supplied as porous pellets dusted with amorphous silica. Another useful reinforcing agent available commercially is Hypro RLP 200X168VTM, a reactive liquid polybutadiene polymer terminated with methacrylate groups.

[0040] <Amine> Part A of the composition of the present invention includes at least one amine that acts as a catalyst to accelerate or promote the curing of the composition of the present invention. The amine is desirably a tertiary amine or a sterically hindered amine. Suitable amines include, for example, tertiary amines represented by the formula NR3, where R is C 1-10 Alkyl, C 1-18 Aryl, C 7-17 Alkalil, and C 7-15 Suitable hindered amines include HNR2 or H2NR (R is C 4-10 Also included are primary or secondary amines such as alkyl groups. For example, alkyl groups such as tertiary butyl, neopentyl, etc., sterically shield the hydrogen attached to the nitrogen atom and are suitable substituents in this component of the invention. In both tertiary and secondary amines, the R group may be attached so that the nitrogen is embedded within a ring structure.

[0041] Particularly useful amines for inclusion in the compositions of the present invention include, for example, 1,8-diazabicyclo(5.4.0)undec-7-ene (DBU), 1,4-diazabicyclo(2.2.2)octane (DABCO), triethylamine, and substituted guanidines such as tetramethylguanidine (TMG), dimethyl-p-toluidine (DMPT), dimethylaniline, dihydroxyethylaniline, dihydroxyethyl-p-toluidine, dimethyl-o-toluidine, dialkylanilines, dialkyltoluidines, acylthioureas, benzoylthioureas, and arylthioureas.

[0042] The amine can be present in an amount of about 0.01 weight percent to about 5 weight percent. Desirably, the amine is present in an amount of about 0.05 weight percent to about 2 weight percent. More desirably, the amine is present in an amount of about 0.3 weight percent to about 0.7 weight percent.

[0043] The composition of the present invention may also desirably include an acid or acid ester. Suitable acids or acid esters include phosphoric acid or its derivatives, phosphoric acid esters, and sulfonic acid or its derivatives. The preferred reactive acid component is a phosphoric acid ester. The acid monomer is a free radically polymerizable acid monomer such as an ethylenically unsaturated mono- or polycarboxylic acid, maleic acid, crotonic acid, and the like. Desirable ones include methacrylic acid (MAA) and acrylic acid. The active acid component adjusts and slows down the cure time of the thermosetting composition. The amine component is necessary to cure part (B) containing the epoxy resin, but without the phosphoric acid ester component, the amine-induced curing process is generally too fast for very large parts or laminates, making laminate manufacturing very difficult. In addition, curing too quickly can cause problems during curing such as excessive heat from the exothermic curing reaction, which can lead to inconsistent or non-uniform curing, and the resulting product may have undesirable physical properties such as bubbles, brittleness, or lower tensile strength than if curing were achieved at a more constant rate.

[0044] Suitable phosphate esters include those of the formula: [ka] (In the formula, R 1 is H or CH3, R 2 is H, or the structure: [ka] (In the formula, R 1 is represented by H or CH3). Particularly useful phosphate esters are hydroxyethyl methacrylate (HEMA) phosphate esters, sold under the trademarks T-MULZ 1228 or HARCRYL 1228 or 1228M, respectively, available from Harcross Chemicals, Kansas City, Kansas. Also included are structures with at least one strong acid "active hydrogen" group, or structures with at least one phosphonic acid active hydrogen group (R1R2POOH), such as hydroxylethyl diphosphonic acid, phosphonic acid, and derivatives, or oligomeric or polymeric structures with phosphonic acid functionality or similar acid strength functionality.

[0045] The part (A) composition desirably also includes a free radical polymerization inhibitor to prevent premature reaction of part (A) prior to mixing. Many suitable free radical polymerization inhibitors are known in the art, including quinones, hydroquinones, hydroxylamines, nitroxyl compounds, phenols, amines, arylamines, quinolones, phenothiazines, and the like. Particularly useful free radical inhibitors include hydroquinone, tertiary butyl hydroquinone (TBHQ), methyl hydroquinone, hydroxyethyl hydroquinone, phenothiazines, and NAUGARD-R (a blend of N-alkyl substituted p-phenylenediamines from Crompton Corp.). One or more individual free radical inhibitor components may also be combined.

[0046] <Other additives> Parts (A) and (B) may also contain additional additives such as fillers, other core-shell polymers, lubricants, thickeners, colorants, etc. Fillers add bulk without sacrificing strength to the adhesive and can be selected from high or low density fillers. Certain fillers, such as silica, can also provide rheology modification or small particle reinforcement. Commercially available examples include Cab-O-Sil 610 under the Cab-O-Sil brand and AEROSIL R8200 under the AEROSIL brand. Of particular interest are the low density fillers.

[0047] Part (B) <Epoxide> Useful epoxy components include, but are not limited to, cycloaliphatic epoxides, epoxy novolac resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol A epichlorohydrin-based epoxy resins, alkyl epoxides, limonene dioxide, and polyepoxides. A preferred resin component is a cycloaliphatic epoxide sold by Dow Chemical under the brand name CYRACURE UVR-6110. The structure of UVR-6110 is: [ka]

[0048] Another suitable resin component is a bisphenol-based liquid epoxy resin such as those sold by Dow Chemical under the trade name "DER." For a description of these epoxy resins, see http: / / epoxy.dow.com / epoxy / products / prod / liquid.htm. Examples of "DER" products suitable for the present invention include DER332 (diglycidyl ether of bisphenol A), DER330 (low viscosity, undiluted, bisphenol A liquid epoxy resin), DER383 (low viscosity, undiluted, bisphenol A liquid epoxy resin), DER354 (standard, bisphenol F based liquid epoxy resin), DER351 (low viscosity, liquid bisphenol A / F resin blend), DER352 (low viscosity, liquid bisphenol A / F resin blend), DER324 (aliphatic glycidyl ether reactive diluent, modified liquid epoxy resin), DER323 (aliphatic glycidyl ether reactive diluent, modified liquid epoxy resin), DER325 (aliphatic glycidyl ether reactive diluent, modified liquid epoxy resin) and DER353 (aliphatic glycidyl ether reactive diluent, modified liquid epoxy resin). Another brand of bisphenol-based liquid epoxy resin suitable for use in the present invention is EPON Resin 828, derived from bisphenol A and epichlorohydrin and available from Hexion Specialty Chemicals, see http: / / www.hexionchem.com / pds / E / EPONTM Resin 828.pdf.

[0049] Another suitable resin component is epoxy novolac resin, which is a product of epichlorohydrin and phenol formaldehyde novolac, sold by Dow Chemical under the trade name DEN. For a description of these epoxy resins, see http: / / epoxy.dow.com / epoxy / products / prod / nov.htm. Examples of "DEN" products suitable for the present invention include DEN431 (low viscosity semi-solid epoxy novolac resin) and DEN438 (semi-solid epoxy novolac resin). Other suitable epoxy resins include polyepoxides that can be cured with a catalyst or hardener at room temperature or at a suitable elevated temperature. Examples of these polyepoxides include polyglycidyl ethers and poly(3-methylglycidyl) ethers obtained by reacting a compound containing at least two free alcoholic hydroxyl groups and / or phenolic hydroxyl groups per molecule with a suitable epichlorohydrin under alkaline conditions or in the presence of an acid catalyst, followed by treatment with alkali. These ethers are derived from acyclic alcohols such as ethylene glycol, diethylene glycol, higher poly(oxyethylene) glycols, propane-1,2-diol, poly(oxypropylene) glycol, propane-1,3-diol, butane-1,4-diol, poly(oxytetramethylene) glycol, pentane-1,5-diol, hexane-2,4,6-triol, glycerol, 1,1,1-trimethylolpropane, pentaerythritol, sorbitol, poly(epichlorohydrin); from alicyclic alcohols such as resorcinol, quinitol, bis(4-hydroxycyclohexyl)methane, 2.2-bis(4-hydroxycyclohexyl)propane, 1,1-bis(hydroxymethyl)cyclohex-3-ene; and from alcohols with aromatic nuclei such as N,N-bis(2-hydroxyethyl)aniline, pip'-bis(2-hydroxyethylamino)diphenylmethane.Alternatively, they may be prepared from mononuclear phenols such as resorcinol and hydroquinone, and polynuclear phenols such as bis(4-hydroxyphenyl)methane, 4,4'-dihydroxydiphenyl, bis(4-hydroxyphenyl)sulfone, 1.1.2.2-tetrabis(4-hydroxyphenyl)ethane, 2.2.-bis(4-hydroxyphenyl)propane (also known as bisphenol A), 2.2-bis(3,5-dibromo-4-hydroxyphenyl)propane, and phenols such as novolaks formed from aldehydes such as formaldehyde, acetaldehyde, chloral, furfuraldehyde, and phenol itself, and phenols whose rings are substituted with chlorine atoms or alkyl groups each containing up to nine carbon atoms (e.g., 4-chlorophenol, 2-methylphenol, 4-t-butylphenol, etc.).

[0050] Poly(N-glycidyl) compounds include, for example, those obtained by dehydrochlorination of reaction products of epichlorohydrin with amines containing at least two amino hydrogen atoms, such as aniline, n-butylamine, bis(4-aminophenyl)methane, bis(4-methylaminophenyl)methane, triglycidyl isocyanurate, and N,N'-diglycidyl derivatives of cyclic alkylene ureas, such as ethylene urea and 1,3-propylene urea, and hydantoins, such as 5,5-dimethylhydantoin.

[0051] Epoxide resins with 12 epoxide groups attached to different types of heteroatoms can be used, such as the N,N,O-triglycidyl derivative of 4-aminophenol, the glycidyl ether-glycidyl ester of salicylic acid, N-glycidyl-N'-(2-glycidyloxypropyl)-5,5-dimethylhydantoin, and 2-glycidyloxy 1,3-bis(5,5-dimethyl-1-glycidylhydantoin-3-yl)propane.

[0052] Also suitable are epoxides derived from oils such as epoxidized soybean oil, epoxidized castor oil, etc. Also suitable are epoxides which are or can be derived from peracid oxidation of unsaturation, including epoxidized liquid rubbers.

[0053] <Peroxide> Benzoyl peroxide itself is a preferred option for use in part (B). Commercially available benzoyl peroxide-containing compositions may also be used. Benox-50 210 Blue (45 Syrigis Performance Initiators, Inc. Helena, AR), a peroxide paste believed to contain 49-50% benzoyl peroxide, is one preferred option. Benox-55 108 White, a peroxide paste believed to contain 54-56% benzoyl peroxide, is another preferred option. Yet another preferred option is Varox 50 A SNS from RT Vanderbilt, Norwalk, Connecticut, a peroxide paste believed to contain 55% benzoyl peroxide.

[0054] <Plasticizer> A plasticizer can be used in part (B) of the two-part composition. As mentioned above, a plasticizer may also be used in part (A). A plasticizer can be any liquid or soluble compound that aids in the flexibility of the reactive composition and / or acts as a carrier medium for the other components of the composition.Examples include aromatic sulfonamides, aromatic phosphate esters, alkyl phosphate esters, dialkyl ether aromatic esters, polymeric plasticizers, dialkyl ether diesters, polyglycol diesters, tricarboxylic acid esters, polyester resins, aromatic diesters, aromatic triesters (trimellitates), aliphatic diesters, epoxidized esters, chlorinated hydrocarbons, aromatic oils, alkyl ether monoesters, naphthenic oils, alkyl monoesters, paraffin oils, silicone oils, di-n-butyl phthalate, diisobutyl phthalate, etc. phthalate, di-n-hexyl phthalate, di-n-heptyl phthalate, di-2-ethylhexyl phthalate, 7C,-9C-phthalates (linear and branched), diisooctyl phthalate, linear 6C-10C phthalate, diisononyl phthalate, linear 7C-10C phthalate, diisodecyl phthalate, linear 9C-11C phthalate, diundecyl phthalate, diisodecyl glutarate, di-2-ethylhexyl adipate, di-2-ethylhexyl azelate, di-2-ethylhexyl sebacate, di-n-butyl sebacate, Diisodecyl adipate, triethylene glycol caprylate, triethylene glycol 2-ethylhexanoate, dibutoxyethyl adipate, dibutoxyethoxyethyl adipate, dibutoxyethoxyethyl formal, dibutoxyethoxyethyl sebacate, tri-2-ethylhexyl trimellitate, tri-(7C-9C (linear)) trimellitate, tri-(8C-10C (linear)) trimellitate, triethyl phosphate, triisopropyl phenyl phosphate, tributyl phosphate, 2-ethylhexyl diphenyl phosphate Examples of suitable phosphate phosphates include phenyl phosphate, trioctyl phosphate, isodecyl diphenyl phosphate, triphenyl phosphate, synthetic triaryl phosphate, tributoxyethyl phosphate, tris(chloroethyl) phosphate, butylphenyl diphenyl phosphate, chlorinated organic phosphates, cresyl diphenyl phosphate, tris(dichloropropyl) phosphate, isopropyl phenyl diphenyl phosphate, trixylenyl phosphate, tricresyl phosphate, and diphenyl octyl phosphate.

[0055] <Block copolymer> The block copolymer may be any block copolymer capable of contributing to the physical properties desired in the disclosed compositions. The block copolymer may be used in either part (A) or part (B).

[0056] Block copolymer rubbers can be constructed using blocks of butadiene or isoprene and styrene (e.g., SBS, SIS, SEBS, and SB) and are commercially available from Shell Chemical Co. as KRATON D-1116 and other KRATON D grade elastomers, and from Dexco as elastomers such as VECTOR 2411IP.

[0057] Other elastomers soluble in methacrylate / acrylate monomers and having a Tg below about 25° C. can be used in place of the polychloroprene and / or block copolymer rubbers, such as epichlorohydrin homopolymers and copolymers with ethylene oxide available from Zeon Chemicals as HYDRIN, acrylate rubber pellets available from Zeon as HYTEMP, polyisoprene rubber, polybutadiene rubber, nitrile rubber, and SBR rubber (random copolymer of butadiene and styrene).

[0058] Still other block copolymers include styrene maleic anhydride copolymers represented by the formula: [ka]

[0059] Styrene maleic anhydride copolymers are well known, some of which are commercially available, for example, under the trade name SMA EFS0 from Sartomer Company, Inc. of Exton, Pa. Styrene maleic anhydride copolymers are the copolymerization products of styrene and maleic anhydride and are characterized by alternating blocks of styrene and maleic anhydride moieties.

[0060] Amphiphilic block copolymers are particularly desirable. Arkema sells amphiphilic block copolymers under the trademark NANOSTRENGTH. Currently, there are two versions of such block copolymers: SBM and MAM. SBM copolymers are reported to be made of polystyrene, 1,4-polybutadiene, and syndiotactic poly(methyl methacrylate).

[0061] Additionally, polymeric materials composed of polymethyl methacrylate ("PMMA") and polybutyl acrylate ("PB") can also be used. This class of polymeric materials is called polymethyl methacrylate-block-polybutyl acrylate-block polymethyl methacrylate copolymers (MAM). Arkema reports that MAMs are triblock copolymers, composed of approximately 70% PMMA and 30% PB. MAMs are composed of separate segments, with the ability to self-assemble at the molecular level. That is, M gives the polymer its hardness, while A gives it its elastic properties. The hard polymer segments tend to dissolve in the (meth)acrylate, while the elastomeric segments provide toughness to the polymeric (meth)acrylate that is formed upon curing. MAMs also enhance mechanical properties without compromising inherent physical properties. MAMs are commercially available under the trade name NANOSTRENGTH and are currently available in several grades, including E-21 and M-52N.

[0062] Arkema advertises its NANOSTRENGTH product line as an acrylic block copolymer that is miscible with many polymers, most of which are major industrial epoxy resins, according to the manufacturer. Also see U.S. Pat. No. 6,894,113. In the patent abstract, the '113 patent describes a thermoset material with improved impact resistance. The impact resistance is obtained from 1-80% of an impact modifier that includes at least one copolymer that includes SBM, BM, and MBM blocks, where each block is bonded to each other by a covalent bond or from an intermediate that is bonded to one of the blocks by a covalent bond and to the other block by another covalent bond, M is a PMMA homopolymer or copolymer that includes at least 50% by weight of methyl methacrylate, B is incompatible with the thermoset resin and the M block and has a glass transition temperature Tg that is lower than the operating temperature of the thermoset material, and S is incompatible with the thermoset resin, the B block, and the M block and has a Tg or melting point that is higher than the Tg of B.

[0063] Another commercially available example of an amphiphilic block copolymer is a polyether block copolymer known in the industry as FORTEGRA 100 from Dow Chemical Co. Dow describes FORTEGRA 100 as a low viscosity toughening agent designed as a low viscosity hardener for use as a highly efficient second phase in amine cured epoxy systems. FORTEGRA 100 is reported to improve toughness without significantly affecting the viscosity, glass transition temperature, corrosion resistance, cure speed, or chemical resistance of the final coating or composition. Since FORTEGRA 100 does not participate in the epoxy curing reaction, it is also reported to be useful in formulation into standard bisphenol A and bisphenol F epoxy systems. As a second phase toughening agent, FORTEGRA 100 is advertised as effective when formulated at specific volume fractions of the finished film or part, typically 3% to 8% of the dry volume is said to provide toughening benefits.

[0064] Additional block copolymers may contain both hydrophobic and hydrophilic segments, or may have the general formula -[(R 1 ) v -(R 2 ) w ] n - (In the formula, R 1 are independently a hydrophobic olefin, such as ethylene, propylene, 1-butene, 1-hexene, 3-methyl-1-pentene, or a polymerizable hydrophobic aromatic hydrocarbon, such as 4-methyl-1-pentene, or styrene; Each R 2 is a hydrophilic acid anhydride such as maleic anhydride, v is 1 to 12, w is 1 to 6, and n is 1 to 50. Contains parts of:

[0065] <Other additives> Parts (A) and (B) may contain additional additives such as fillers, lubricants, thickeners, colorants, etc. The fillers add bulk without sacrificing strength of the adhesive and can be selected from high density or low density fillers.

[0066] <Packaging> Parts (A) and (B) are each packaged in a separate container such as a bottle, can, tube, drum, etc. Parts (A) and (B) are mixed in a weight ratio of about 3-50 parts (A) to 1 part (B). Preferably, the weight ratio of parts (A) and (B) is about 5-20 parts (A) to 1 part (B).

[0067] The two parts can be mixed using a mixing nozzle that has fluid inputs for the two components, performs the appropriate mixing operation, and dispenses the adhesive mixture directly onto the surface to be bonded. An example of a commercially available mixing and dispensing device is the MIXPAC®, sold by ConProTec, Salem, New Hampshire. The two parts can also be mixed manually in a bowl or bucket, but the operator must ensure that the mixture is thoroughly mixed. To ensure complete mixing, each part can be formulated with a dye or pigment that will form a third color after mixing. For example, if one part contains a yellow dye and the other contains a blue dye, the entire adhesive composition will be green after mixing.

[0068] The term "curing" refers to the chemical reaction that converts the fluid mixture into the solid combination of the present invention. The curing process of this composition is exothermic and can reach temperatures on the order of about 120°C when using large adhesive beads. EXAMPLES

[0069] Loctite HHD8540 is a commercially available two-part structural adhesive that is used as a comparison for the compositions of the present invention. In each of the following inventive examples, a methyl methacrylate-butadiene-styrene core-shell toughening additive of the present invention was used in place of or in addition to one or more toughening agents in the Loctite HHD8540 composition, as shown in the table below.

[0070] Part (B) of the commercial composition Loctite HHD8540 was held constant for all compositions, as shown for each of the compositions of the present invention set out in the table below.

[0071] The mixing ratio of Part (A) to Part (B) by weight was 10:1. The mixed product was cured at 45°C for 20 minutes and then left at room temperature for 24 hours before testing.

[0072] <Test> Izot impact resistance was performed using ASTM D6110-18 using dual size aluminum lapshears.

[0073] For side impact resistance, grit blasted mild steel (GBMS) lap shears with a 5 mil gap were used. Side testing was performed using a drop tower impact tester and recorded by an instrumented tap. A known mass is dropped end-on onto the bonded lap shear assembly at a specified velocity. The force required to break the adhesive bond is recorded by the instrumented tap. Side impact testing was performed based on GM9751PRev. August 2014 General Motors Engineering Standards Side Impact Test.

[0074] All compositions tested in the examples used the following Part (B) composition: [Table 2]

[0075] <Example 1> Table 1 shows commercially available prior art compositions and inventive compositions 1 to 4. Each of the inventive compositions further comprises a core-shell impact modifier. [Table 3] TIFF2025503226000009.tif30170

[0076] Each of the compositions in Table 1 was tested for Izod impact resistance.

[0077] Test results are shown in Table 2. Compositions 1-3 incorporated a methacrylate-compatible core-shell component in combination with another toughening agent component. As can be seen from the test values, compositions 1-4 of the present invention exhibited impact resistance equal to or greater than that of the commercially available compositions containing the toughening agents Kraton D1155 and Hypro RLP2000X168VTB, which are not miscible with methyl methacrylate.

[0078] [Table 4]

[0079] <Example 2> [Table 5]

[0080] Each of compositions 4 and 5 of the present invention was formulated as shown in Table 3 above and subjected to side impact testing, the results of which are shown in Table 4. As shown in Table 4, the formulation of 13-15 parts by weight of a shell core reinforcing component and one or more immiscible toughening agents provided side impact results comparable to the commercially available Henkel composition containing only the immiscible toughening agents.

[0081] [Table 6]

[0082] <Example 3> [Table 7]

[0083] Composition 7 in Table 5 above contained 15 parts by weight of a core-shell component in addition to Kraton D1155 and Hypro 1300X33LC VTBNX, both of which are immiscible reinforcing components.

[0084] Surprisingly, side impact testing showed that the combination of Kraton D1155 with Hypro1300X33LC VTBNX and the core-shell component improved impact resistance by 53%.

[0085] [Table 8]

[0086] <Example 4> [Table 9]

[0087] Similar to Example 3, inventive composition 8 also contained a combination of core-shell components, Kraton D1155 and Hypro 1300X43LC VTBNX. Side impact test results (Table 8) showed an increase in side impact resistance of about 54%.

[0088] [Table 10]

[0089] <Example 5> [Table 11]

[0090] Composition 9 of the present invention includes a core shell reinforcing component in combination with about 22 parts by weight of Blendex 338 (ABS rubber particles) and 13 parts by weight of Hypro RLP2000X1.

[0091] Composition 10 of the present invention contained about 6.45 parts by weight of the core-shell reinforcing component, which included 4.92 parts by weight of Blendex 338, and 22 parts by weight of Kraton D1155.

[0092] Side impact testing of compositions 9 and 10 show approximately 41% improvement in side impact resistance, respectively, compared to the commercial Henkel product containing only the immiscible toughening agent. [Table 12]

Claims

1. a) i. (Meth)acrylate component ii. about 10% to about 25% by weight of the total composition of a core-shell impact modifier comprising a polymer core and at least two polymer layers surrounding the core, each layer having a different polymer composition than the other layers, at least one polymer layer comprising a polymer that is a gradient polymer, the gradient polymer being a copolymer of at least two different monomers (A) and (B) having a gradient of repeat units arranged from predominantly monomer (A) to predominantly monomer (B) along the copolymer; iii. about 10% to about 25% by weight of the total composition of a reinforcing component selected from the group consisting of polybutadiene rubber particles (Kraton D), liquid methacrylate terminated polybutadiene polymer (Hypro RLP), and combinations thereof; iv. Amines A first part including b) i. an epoxy, and ii. Peroxide The second part includes An adhesive composition comprising: An adhesive composition which, upon curing, exhibits at least a 50% increase in side impact strength compared to a substantially identical composition lacking the impact modifier.

2. 10. The composition of claim 1, wherein upon curing, the composition exhibits at least a 60% increase in side impact strength compared to a substantially identical composition without the impact modifier.

3. 2. The adhesive composition of claim 1, wherein the core-shell impact modifier comprises particles having a particle size of 170-350 nm comprising one polymeric rubber core comprising at least partially crosslinked isoprene or butadiene and optionally styrene, and at least two polymeric layers, at least one of which is an outermost thermoplastic shell layer having a Tg greater than 25° C., each layer having a different polymer composition.

4. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core surrounded by a polymeric layer, the polymeric core layer having a glass transition temperature below 0° C. and a different polymer composition than the polymeric rubber core, the polymeric core layer being a gradient zone.

5. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core having a glass transition temperature of less than about -40°C.

6. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core having a glass transition temperature of from about -80°C to about -40°C.

7. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core comprised of polybutadiene.

8. 10. The composition of claim 1, wherein the core-shell impact modifier comprises a polymeric rubber core composed of butadiene and styrene.

9. The (meth)acrylic component of part (a) is selected from the group consisting of methyl (meth)acrylate, (meth)acrylic acid, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. , nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, tolyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, stearyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate, 2-(meth)acryloyloxypropyltrimethoxysilane Ran, (meth)acrylic acid ethylene oxide adduct, trifluoromethylmethyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, 2-perfluorohexadecylethyl (meth)acrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, dipentaerythritol monohydroxypentaacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6- Hexanediol diacrylate, neopentyl glycol diacrylate, pentaerythritol tetraacrylate, 1,2-butylene glycol diacrylate, trimethylolpropane ethoxylate tri(meth)acrylate, glyceryl propoxylate tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, tri(propylene glycol) di(meth)acrylate, neopentyl glycol propoxylate di(meth)acrylate, 1,The composition of claim 1, wherein the di(meth)acrylate is selected from the group consisting of 4-butanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, and combinations thereof.

10. 10. The composition of claim 1, wherein the reinforcing component comprises polybutadiene rubber particles and a liquid methacrylate-terminated polybutadiene polymer.

11. 2. The composition of claim 1, wherein the amine is selected from the group consisting of 1,8-diazabicyclo(5.4.0)undec-7-ene, 1,4-diazabicyclo(2.2.2)octane, triethylamine, tetramethylguanidine, dimethyl-p-toluidine, dimethylaniline, dihydroxyethylaniline, dihydroxyethyl-p-toluidine, dimethyl-o-toluidine, dimethylaniline, and benzoylthiourea, trialkylamines, tributylamine, dihydropyridine, phenyldihydropyridine, dihydropyridine derivatives, aldehyde condensation products of alkyl, aromatic, heterocyclic amines, and combinations thereof.

12. The composition of claim 1 further comprising a (meth)acrylate terminated polyurethane component.

13. The composition of claim 1 further comprising a triarylphosphine or an alkylarylphosphine.

14. 14. The composition of claim 13, wherein the phosphine is selected from the group consisting of tri(o-tolyl)phosphine, tris(4-methoxyphenyl)phosphine, diphenyl(p-tolyl)phosphine, diphenyl(o-tolyl)phosphine, tris(o-methoxyphenyl)phosphine, tri(p-tolyl)phosphine, diphenyl(2-methoxyphenyl)phosphine, tris(3,5-dimethylphenyl)phosphine, and triphenylphosphine.

15. 2. The composition of claim 1, wherein the first and second parts are in a weight ratio of first part (a) to second part (b) of about 10 to about 1.

16. 10. The composition of claim 1, further comprising a free radical stabilizer selected from the group consisting of quinones, hydroquinones, and combinations thereof.

17. 10. The composition of claim 1 further comprising a free radical stabilizer selected from the group consisting of hydroquinone, tertiary butyl hydroquinone, phenothiazine, methyl hydroquinone, hydroxyethyl hydroquinone, N-alkyl substituted p-phenylenediamines, and combinations thereof.

18. 10. The composition of claim 1, further comprising a component selected from the group consisting of plasticizers, fillers, block copolymers, thixotropic agents, rheology modifiers, viscosity modifiers, adhesion promoters, diluents, monomers, oligomers, and combinations thereof.

19. 1. A method for adhering a first surface to a second surface, comprising the steps of: Providing a two-part adhesive composition according to claim 1, providing a first surface to be bonded and a second surface to be bonded; dispensing, with mixing, the two-part adhesive composition onto at least one of the first surface or the second surface; bonding the first surface and the second surface with an adhesive composition between the first surface and the second surface; forming an adhesive bond therebetween.

20. 20. The method of claim 19, wherein the first and second parts are mixed in a weight ratio of first part (a) to second part (b) of about 10 to about 1.

21. a) i. (Meth)acrylate component ii. about 10% to about 25% by weight of the total composition of a core-shell impact modifier comprising a polymer core and at least two polymer layers surrounding the core, each layer having a different polymer composition than the other layers, at least one polymer layer comprising a polymer that is a gradient polymer, the gradient polymer being a copolymer of at least two different monomers (A) and (B) having a gradient of repeat units arranged from predominantly monomer (A) to predominantly monomer (B) along the copolymer; iii. about 10% to about 25% by weight of the total composition of a reinforcing component selected from the group consisting of polybutadiene rubber particles, liquid methacrylate-terminated polybutadiene polymers, and combinations thereof; iv. Amines A first part including b) i. an epoxy, and ii. Peroxide The second part includes An adhesive composition comprising the reaction product of An adhesive composition which, upon curing, exhibits at least a 50% increase in side impact strength as compared to a substantially identical composition lacking the impact modifier.